Estimate of undergraduate university student alcohol use in China: a systematic review and meta-analysis - Ian Newman; Lanyan Ding; Yonghua Feng (BMC, 2017)
Abstract Objective To develop an estimate of self-reported last 30 day alcohol use by university students in China. Methods A search of papers published in English and Chinese between 2006 and 2015, following pre-established selection criteria, identified 30 papers that were included in this meta-analysis. Nine moderator variables were preselected for this analysis. Results A total of 749 papers were identified in the keyword search, and 30 studies (28 in Chinese, 2 in English) met all selection criteria and were included in the meta-analysis. The self-reported last-30-day alcohol use for undergraduate university students was 66.8% for males and 31.7% for females. Meta-regression identified three moderators associated with the different drinking rates reported: the definition of drinking, the origin of the questionnaire used in the survey, and the geographic region where the survey was conducted. These three moderators explained 56% of the heterogeneity of reported drinking rates for the male students and 47% of the heterogeneity of reported drinking rates for the female students. Conclusions The results of this meta-analysis provide an estimate of last 30 day alcohol use by university students (age 18-23) and increase our understanding of drinking by young people in China. The meta-analysis suggested three variables that could have affected the results and which are worthy of further study. The discussion places these results in the context of Chinese drinking culture and university life.